The Effect of Topography on Settlement Patterns in The Nusa Penida Island, Bali, Indonesia - I Kadek Merta Wijaya, Syamsul Alam Paturusi ,Ngakan Ketut Acwin Dwijendra, I Made Adhika (International Journal of Modern Agriculture, 2021)
Nusa Penida Island's physical condition is an area with dry, calcareous, and steep topography, valley also hilly. Nusa Penida Island consists of 16 villages scattered in clusters in the northern and southern regions with coastal and hilly areas. The settlements in the south of the part have an organic settlement pattern following the pattern and height also the type of soil from the topography of the area. This research aimed to examine the topographical aspects of villages' settlement patterns in the southern part of Nusa Penida Island. The method used in this research is qualitative content analysis through an approach to the content aspects of studies on Nusa Penida, empirical conditions, and aerial photography analysis. The sample selection was limited by purposive sampling to two villages, namely Tangled Village and Batukandik Village. The results of this study indicate that there is a harmonious and integrated relationship between settlements and land: (1) the zone of worship (shrines/temples) and residential zones of houses; (2) rocky soil type as an option in residential construction; (3) soil layer with minimal rock content as an alternative to agricultural land; and (4) have an organic settlement pattern.